Preserving Tradition and Social Interaction in the Era of Digitalization: A Study of the Kampung Naga Community in Tasikmalaya - Samsul Arip; Saifudin Asrori (GoAcademica Research & Publishing, 2026)
The development of digital technology has brought significant changes to various aspects of social life, including indigenous communities. Digitalization provides easier access to information and communication; however, it simultaneously poses challenges to the sustainability of traditional values, cultural practices, and long-established patterns of social interaction. This article aims to analyze how the indigenous community of Kampung Naga maintains its traditions and social interactions amid the increasingly strong wave of digitalization, particularly in the post-Covid-19 pandemic era. This study employed a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews with traditional leaders, religious leaders, youth representatives, and local community members of Kampung Naga, as well as supported by documentation studies. The data were analyzed interactively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the Kampung Naga community does not entirely reject digitalization; instead, they implement a strategy of selective adaptation. Digital technology is utilized in a limited manner for specific purposes, such as communication and education, without disrupting customary structures and traditional values. Traditions, mutual cooperation, and adherence to ancestral values remain the primary foundations in maintaining social integration. These findings reinforce Talcott Parsons’ structural functionalism perspective, particularly the AGIL scheme, which emphasizes that a social system can survive by adapting to change without losing its value integration.